ChemInform Abstract: Facile One‐Pot Synthesis of 3, 5‐Disubstituted 1H‐Pyrazoles from Propargylic Alcohols via Propargyl Hydrazides. Issue 26 (6th June 2013) - Reddy, Chada Raji; Vijaykumar, Jonnalagadda; Gree, Rene
Abstract The procedure consists of acid‐catalyzed N‐propargylation of TSA with propargylic alcohols and subsequent base‐promoted cyclization.